2001
DOI: 10.1073/pnas.201393798
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exposure to pregnancy levels of estrogen prevents mammary carcinogenesis

Abstract: It is well established that pregnancy early in life reduces the risk of breast cancer in women and that this effect is universal. This phenomenon of parity protection against mammary cancer is also observed in rodents. Earlier studies have demonstrated that shortterm administration of estradiol (E) in combination with progesterone mimics the protective effect of parity in rats. In this study, the lowest effective E dosage for preventing mammary cancer was determined. Rats were injected with N-methyl-N-nitrosou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 41 publications
(43 reference statements)
3
77
0
Order By: Relevance
“…However, newer evidence suggests that the protective effect may be short-term tissue exposure to pregnancy-level estrogen. 94 Physiologically, endogenous hormones contribute to development of the terminal ductal lobular unit in the breast-the site of origin for both benign and malignant breast tumors that result from cellular proliferation. 95 Pregnancy accelerates the development and maturity of terminal ductal lobular units.…”
Section: Effect Of Pregnancymentioning
confidence: 99%
“…However, newer evidence suggests that the protective effect may be short-term tissue exposure to pregnancy-level estrogen. 94 Physiologically, endogenous hormones contribute to development of the terminal ductal lobular unit in the breast-the site of origin for both benign and malignant breast tumors that result from cellular proliferation. 95 Pregnancy accelerates the development and maturity of terminal ductal lobular units.…”
Section: Effect Of Pregnancymentioning
confidence: 99%
“…Physiologic levels of 17h-E in premenopausal women ranges from 30 to 300 pg/mL midcycle (0.1-1 nmol/L), whereas higher levels of estrogen (100 nmol/L) may be found in pregnant women. Nulliparous women are more susceptible to breast cancer, and it was suggested that short-term exposure to high pregnancy levels of estrogen may in fact reduce mammary carcinogenesis (26), whereas longer-term estrogen exposure to lower concentrations may result in carcinogenesis. Micromolar concentrations of estrogen have been shown to inhibit proliferation of rhesus ovarian surface epithelial cells (27), via the blocking of serum growth factors, activation of the G 1 -phase cell cycle checkpoint, and induction of p21, possibly through the up-regulation of p53.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the effects of E and P given singly were tested to determine the ability of these hormones to induce protection from mammary carcinogenesis in a post-treatment model (Rajkumar et al 2001). It was shown that treatment with E2 alone, at a critical dose of 100 mg/silastic tubing, provided a pregnancy level of circulating E2 and a protection from mammary carcinogenesis compared with the AMV.…”
Section: Protective Effect Of Pregnancymentioning
confidence: 99%